Revisiting leadership in information and communication technology (ICT)-enabled activism: A study of Egypt's grassroots human rights groups. (May 2019) - Azer, Evronia; Harindranath, G; Zheng, Yingqin
Scholars argue that contemporary movements in the age of social media are leaderless and self-organised. However, the concept of connective leadership has been put forward to highlight the need for movements to have figures who connect entities together. This study conducts a qualitative research of 30 interviews of human rights groups in the 2011 Egyptian revolution to address the question of how leadership is performed in information and communication technology–enabled activism. The article reconceptualises connective leadership as decentred, emergent and collectively performed, and provides a broader and richer account of leaders' roles, characteristics and challenges.